The Dynamics of Working Hours and Wages Under Implicit Contracts - Marco Guerrazzi; Pier Giuseppe Giribone (Global Labor Organization (GLO), 2021)
In this paper, we explore the dynamics of working hours and wages in a model economy where a firm and its workforce are linked to each other by an implicit contract. Specifically, we develop a deterministic and a stochastic framework in which the firm sets its level of labour utilization by considering that workers' earnings tend to adjust in the direction of a fixed level. Without any uncertainty in firm's profitability, we show that the existence and the properties of stationary solutions rely on factors that usually determine the enforceability of contracts and we provide evidence that wages tend to move countercyclically towards the allocation preferred by the firm. Moreover, we show that adding uncertainty does not overturn the counter-cyclical pattern of wages but is helpful in explaining their dynamic behaviour in response to demand shocks as well as their typical stickiness observed at the macro level.
Keywords: D86; E24; J41; 330; Implicit contract theory; Consumption smoothing; Out-of-equilibrium dynamics; Stochastic optimal control